Valorisation des coques de noyaux de Balanites aegyptiaca (L.) Del. et Hyphaene thébaica (L.) Mart. pour l’élaboration et caractérisation de Charbons Actifs; application pour l’élimination du chrome - Ousmaila, Sanda Mamane; Maâzou, Siragi Dounounou Boukari; Mousbahou, Malam Alma Maman; Ibrahim, Natatou (European Scientific Journal, ESJ, 2018)
This paper focuses on the development and characterization of activated carbons to agro-food waste by activation with ortho phosphoric acid, and its application in the elimination of chromium in solution. The functions were determined by Bohem's method. The thermal analysis was carried out on the hulls of waste. The specific surface area and the pore volume are determined according to the method of Brunauer, Emmet and Teller and the method of Barret, Joyner and Halenda respectively. The Lagergren and Ho and McKay models were used for the kinetic study of chromium removal. Those of Langmuir and Freundlich have to do with the study of isotherms and the law of Van't Hoff and Gibbs in relation to the determination of thermodynamic parameters. The results obtained show that the surface functions are acidic in nature. Activated carbon from balanites aegyptiaca has developed a specific surface (1560.7401 m2 g -1 ) that exceeds that of Hyphaene thebaica (722.1510 m2 g -1 ). The pseudo-order 2 kinetics (Ho and McKay) better describe the adsorption with correlation coefficients close to unity. Adsorption capacities and rate constants prove rapid adsorption at the early stages. For the isotherms, the calculated parameter values are much more consistent with those of the Langmuir isotherm. ∆Gads 0 < 0 ; the adsorption process is spontaneous. Moreover, the values are in the range of a physisorption.